Application of lean management in operating room nursing and its impact on improving the on-time start rate of the first scheduled surgery: A pre–post study - Siyuan Yang; Ruodan Zhou; Sanlin Zhang; Wei Xu (Journal of Minimal Access Surgery, 2026)
Abstract Objective: This study sought to evaluate the impact of lean management (LM) on improving the on-time start rate of the first scheduled surgery and overall nursing performance in the operating room. Patients and Methods: A total of 150 patients who received the first scheduled surgery from November 2023 to May 2024 were selected as the observation group and 150 patients who received the first scheduled surgery from May to October 2023 were selected as the control group. The observation group implemented LM, while the control group received routine peri-operative management. Work efficiency indicators, on-time start rates, operating room turnover efficiency, nursing quality scores, patient satisfaction and staff competency levels were compared before and after the implementation of LM. Results: The observation group showed notably reduced surgical duration, preparation time and room acceptance time compared to the control group (all P < 0.001). The on-time start rates of both the first and subsequent surgeries were significantly higher in the observation group (all P < 0.001). In addition, the observation group achieved higher daily surgical volume and surgeries per operating room. Nursing quality assessment scores, patient satisfaction ratings and staff competency scores were all significantly improved following LM implementation (all P < 0.001). Conclusion: Implementation of LM optimises operating room workflow, enhances nursing quality and improves patient satisfaction, indicating that LM is an effective strategy for improving operating room performance.